PENDEKATAN DU PONTSYSTEMPADA PERUSAHAAN INDUSTRIAL DALAM MENILAI EFISIENSI PENGGUNAAN MODAL KERJA TERHADAP KINERJA KEUANGAN PT XYZ 2007-2011 - SAFRI SAFRI; SYAHRUL SYAHRUL (JURNAL TEKNIK INDUSTRI, 2018)
Analysis Du Pont is an analysis system used to control the change in the ratio of activity and net profit margin and how big influence on ROI(Return On Investment), from ratings efficient use of working capital to the performance of XYZ generating efficiency rate of use of working capital is shown by looking at the turnover of working capital and total assets of the company turnover amounted to 7.70. Financial performance in 2007-2011 showed an average level of profitability relative increase each year. The financial performance of PT XYZ in the efficient use of working capital and ROI of 29.77%. The analysis resulted in that company have the financial performance and the level of efficiency of capital use of good work.Keywords: Return on Investment, Net Profit Margin, Analisis Du Pont